Calcium Regulates Growth and Nutrient Absorption in Poplar Seedlings - Weng, Xiaohang; Li, Hui; Ren, Chengshuai; Zhou, Yongbin; Zhu, Wenxu; Zhang, Songzhu; Liu, Liying (Frontiers in Plant Science, 2022)
As a crucial element for plants, calcium (Ca) is involved in photosynthesis and nutrient absorption, and affects the growth of plants. Poplar is an important economic forest and shelter forest species in China. However, the optimum calcium concentration for its growth is still unclear. Herein, we investigated the growth, biomass, photosynthetic pigments, photosynthetic parameters and products, chlorophyll fluorescence parameters, water use efficiency (iWUE), and antioxidant enzyme activity of “Liao Hu NO.1” poplar (P. simonii × P. euphratica) seedlings at 0, 2.5, 5, 10, and 20 mmol·L−1 concentrations of Ca2+, and further studied the absorption, distribution, and utilization of nutrient elements (C, N, P, K, and Ca) in plants. We found that with increasing calcium gradient, plant height and diameter; root, stem, leaf, and total biomasses; net photosynthetic rate (Pn); stomatal conductance (Gs); intercellular carbon dioxide (Ci) level; transpiration rate (Tr); Fv/Fm ratio; Fv/F0 ratio; chlorophyll-a; chlorophyll-b; soluble sugar and starch content; superoxide dismutase (SOD), catalase (CAT), and peroxidase (POD) levels; and long-term water use efficiency (iWUE) of poplar seedlings first increased and then decreased. These parameters attained maximum values when the calcium concentration was 5 mmol·L−1, which was significantly different from the other treatments (P < 0.05). Moreover, a suitable Ca2+ level promoted the absorption of C, N, P, K, and Ca by various organs of poplar seedlings. The absorption of C, N, P, and K increased first and then decreased with the increased calcium concentration, but the optimum calcium concentrations for the absorption of different elements by different organs were different, and the calcium concentration in leaves, stems, and roots increased gradually. Furthermore, the increase in exogenous calcium content led to a decreasing trend in the C/N ratio in different organs of poplar seedlings. C/P and N/P ratios showed different results in different parts, and only the N/P ratio in leaves showed a significant positive correlation with Ca2+ concentration. In conclusion, the results of this study indicate that 5 mmol·L−1 concentration of Ca2+ is the optimal level, as it increased growth by enhancing photosynthesis, stress resistance, and nutrient absorption.